Pengolahan Limbah Kulit Buah Naga Super Merah (Hylocereus Costaricensis) pada Materi Pelajaran Kimia Kelas XI SMA Negeri Muncar Banyuwangi - Ana Nurjanah (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2022)
Research that was tested, students of class XI at Muncar High School (SMA) were able to identify the hydroquinone content in the bleaching cream. Hydroquinone (HQ) is a phenol-derived compound used in the cosmetic industry as a bleaching agent. This compound is very risky & the limits of its use must be controlled. BPOM has decided that the aporism limit for cosmetics is 2%. Hydroquinone more than 5% is a hard drug, the impact of long-term use can cause skin cancer. Hydroquinone can be identified by using a natural marker, namely anthocyanin which is in the dragon fruit skin, by using the method of extracting the dragon fruit skin using a 1.5 M citric acid solvent, a temperature of 450C, where the results are used to analyze the content of the Hydroquinone content in cosmetic creams face bleaching, based on this research, it is proven that cosmetics that are spread in the community positively contain Hydroquinone.